Efecto de la fertilización nitrogenada en el secuestro de carbono de la biomasa aérea del cultivo de maíz (zea mays) M-28T en la E.E. "El Porvenir" - INIA - Bartra García, César Augusto (2003)
In order to quantify the content of carbon sequestered in four stages of development of maize cultivation after planting and determine the effect of nitrogen fertilization in maize, in carbon sequestration; This work was carried out, in the field Experimental of the national program of research of corn of the E. E. "The future" which is located at Km 14.5 South Road "Fernando Belaúnde Terry", Juan Guerra district, province and Department de· San Martin; with a T ° annual maximum of 27 ° C, annual average precipitation of 1 206 mm and a relative humidity of 79%. The design employed was complete block to random (DBCA), with 4 treatments and 4 replications. The treatments were T1 (0 Kg N / has), T2 (40 Kg N / has), T 3 (80 Kg / has) and T4 (120 Kg N / has). Results showed that the mean dose of nitrogen (80 Kg N / has) T3, accumulated more carbon in their bodies with a total of 18 937,60 Kg / ha, comparatively with the higher dose (120 Kg N / has), T4 who accumulated 17 994,8; the same treatments T1 and T2 accumulated 13 835,70 and 952,50 15 Kg / has carbon indicating the lowest. The economic analysis shows that T3 treatment obtained a higher net profit of S /. 271,42 new soles, which represents a relationship benefit cost of 1.11 surpassing all other treatments in study; the utility obtained due to the benefit obtained by the accumulation of carbon in the corn plant; otherwise everything would be loss.